Waahi: a case study of social and economic development in a New Zealand Maori community - Mahuta, R. T. (University of Waikato, Centre for Maori Studies and Research, 1981)
Keywords: economic development; huntly; iwi; marae; māori decision making; ngāti mahuta; rangatiratanga; social life and customs; waikato iwi

Chapter 15: From the Sideline: Tikanga, Treaty Values and Te Papa - Tapsell, Paul (Waitangi Revisited, 2005)
Keywords: bicultural; government relations; history; land tenure; mana whenua; marae; museums; race relations; te papa museum; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty principles

Chapter 1: Tino Rangatiratanga - Durie, Mason (Waitangi Revisited, 2005)
Keywords: constitution; government relations; history; kotahitanga; land tenure; marae; nationhood; race relations; self-governance; tiriti o waitangi/treaty of waitangi

Persisting inequalities and the potential for intervention through ‘new’ governance models: An independent research report - Wiremu, Fiona; Gillies, Annemarie; Mika, Jason; Smith, Graham; Ngawati, Maria (2021)
This report sets out the findings and recommendations from research into Māori governance and its potential to effect change in persistent inequalities that affect Māori. Māori governance is a form of Indigenous governance to be found in Aotearoa New Zealand that gives collective voice and agency to tribal and nontribal aspirations and imperatives at local, regional, national and international levels. Māori governance is, however, constrained by state and nonstate actors, and must adapt accordingly to achieve its development goals. In this research, we use kaupapa Māori theory, which emphasises ‘by Māori for Māori’ research processes that are transformative, grounded in mātauranga Māori, tikanga Māori, and te reo Māori. This research asks: what is the potential for new governance structures to intervene in persisting social, cultural, political and economic inequalities that disproportionately accrue to Māori? Three sub-elements were explored: (1) governance structure, form, function; (2) governance and developmental imperatives; and (3) governance and aspirations. We reviewed the Indigenous and Māori governance literature and conducted case study research of Māori governance from three perspectives: community outcomes at a marae level in a Ngāti Kahungunu, health outcomes at a provider level in the Mataatua district, and Māori economic outcomes in the Manawatū. At the community level, we found that Māori engage in governance using Māori values, Māori knowledge and relationships, in both Māori and non-Māori governance structures to achieve Māori aspirations. Māori governance roles within hapū and iwi need to be more broadly accessible to allow different voices and capabilities to emerge. At a health provider level, we found that health system governance, while inclusive of attempts at partnership arrangements, have not been effective at displacing structural inequities, with particular criticism of the uneven effects of the devolution policy in health for Māori. Covid-19 responses demonstrated that bureaucratic control of Māori governance arrangements could be relaxed with positive effects. In terms of the economic perspective, we found that national policy sees self-determined Māori economic development as effecting change in Māori socioeconomic outcomes. However, Māori representation in the governance of economic development is low, and regionally, Māori economic development is constrained by resource limitations despite the advent of treaty settlements. A focus on collaboration across iwi, capability and intent of Māori business networks, and an equitable share of economic resources will assist.
Keywords: governance; hapū; inequality; iwi; marae; mātauranga māori; tino rangatiratanga

Maori Political Rhetoric - Bargh, Maria (2011)
When considering how Maori political rhetoric fits within the New Zealand political landscape it is necessary to ask what makes such rhetoric distinctive and important. In this paper I examine three areas of distinctly Maori political rhetoric; the unique locations of Maori politics, the formalities to be observed by speakers and the use of particular rhetorical devices by Maori speakers, including the use of Maori language and waiata (song). Given the ways that the distinctive nature of Maori political rhetoric is often undervalued, misinterpreted of misrepresented by many non-Maori, the questions which underlie the discussion here must be around what the implications of this situation are for Maori and non-Maori.
Keywords: kāwanatanga; marae; organising; tino rangatiratanga; turangawaewae; waiata